Uma transição para a gestão ágil de projetos: estudo de caso em uma instituição financeira - Portella, Vitoria de Oliveira (Universidade Federal de São Carlos, 2022)
Since the early 2000s, the agile methodology has been implemented by several technology companies when there is a need for software development. Around 2010, organizations from other branches also started a movement to change project management, in order to make their project processes more flexible and bring communication between the development team and their customers closer. This research aims to analyze the transition of project management methodologies, from traditional to agile, by a non-technology company. The research is exploratory and the method used is the case study, applied to different areas of a company in the means of payment sector. As research instruments, interviews are used with company employees who have important roles in the company's project management transition. The results reveal benefits brought by the implementation of the agile methodology, such as the reduction of project execution time, facilitation of communication between clients and work teams, in addition to faster changes in the project scope when necessary. Some points of reservation and attention are also considered, such as the redefinition of roles in the company's functional structure caused by the change of position in the transition of project methodology and the lack of a standardized method to measure customer satisfaction.
A transition to agile project management: a case study in a financial institution.
Keywords: Gestão ágil; Gestão de projetos; Meios de pagamento; Instituição financeira; Agile management; Project management; Payment options; Financial institution; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO